Technology Adoption in the Garment Industry in Southwestern Vietnam: Integrating Triple Helix and Innovation Diffusion Perspectives - Lam, Huynh Canh Thanh; Thi Ngoc Anh, Nguyen; Thanh Nha, Huynh (VNU Journal of Science: Policy and Management Studies, 2026)
Abstract: Against the backdrop of deepening international integration and mounting pressures for technological transformation and supply chain digitization, this study examines the effectiveness of technology adoption in the garment industry in the Southwestern region of Vietnam, a key economic sector currently confronting significant structural challenges. This study investigates the effectiveness of technology adoption in the garment industry of Southwestern Vietnam through an integrated analytical framework built upon three pillars-technology, human resources, and institutional support. Using a mixed-methods design, the research combines survey data from 54 enterprises in Long An, Tien Giang, Can Tho, and Vinh Long with 32 in-depth interviews with managers and technicians. The results reveal that technological upgrading remains modest and uneven, with foreign-invested enterprises significantly outperforming domestic firms in automation, digitalization, and operational efficiency. Workforce capabilities-particularly digital and technical skills-are insufficient to meet the demands of modern production systems, while policies supporting digital transformation and vocational training vary widely across provinces, leading to fragmented implementation of the Triple Helix model. The study contributes a regionally adapted framework integrating Triple Helix and innovation-diffusion perspectives,and proposes four strategic orientations: strengthening absorptive technological capacity, enhancing Foreign Direct Investment (FDI) - domestic linkages, accelerating digital reskilling, and improving regional institutional coordination. Keywords: Technology adoption; Garment industry; Southwestern Vietnam; Human resources; Triple Helix; Innovation diffusion.